2020
DOI: 10.1101/2020.10.06.327833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinctive alteration of presynaptic proteins in the outer molecular layer of the dentate gyrus in Alzheimer’s disease

Abstract: Synaptic degeneration has been reported as one of the best pathological correlate of cognitive deficit in Alzheimer’s Disease (AD). However, the location of these synaptic alterations within hippocampal sub-regions, the vulnerability of the presynaptic versus postsynaptic compartments, and the biological mechanisms for these impairments remain unknown. Here, we performed immunofluorescence labeling of different synaptic proteins in fixed and paraffin embedded human hippocampal sections and report reduced level… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
1
1
Order By: Relevance
“…Indeed, the genetic deletion, or the loss of function of several presynaptic proteins (e.g., Munc18, α-synuclein, syntaxin1, or SNAP-25) leads to neurodegeneration. [43][44][45][46] Our observation of the selective accumulation of presynaptic proteins in APP accumulations contrasts with recent discoveries from us and others of broad downregulation of presynaptic proteins in AD brains [29][30][31][32] and indicates that the alteration of presynaptic proteins in AD is spatially heterogeneous. In the AD hippocampus, APP follows a complex pattern of misdistribution, too, accumulating within neuropil areas, and vanishing in neuronal somata where APP is normally prominent.…”
Section: Study Conclusion Disease Implications and Therapeutic Opport...contrasting
confidence: 85%
See 1 more Smart Citation
“…Indeed, the genetic deletion, or the loss of function of several presynaptic proteins (e.g., Munc18, α-synuclein, syntaxin1, or SNAP-25) leads to neurodegeneration. [43][44][45][46] Our observation of the selective accumulation of presynaptic proteins in APP accumulations contrasts with recent discoveries from us and others of broad downregulation of presynaptic proteins in AD brains [29][30][31][32] and indicates that the alteration of presynaptic proteins in AD is spatially heterogeneous. In the AD hippocampus, APP follows a complex pattern of misdistribution, too, accumulating within neuropil areas, and vanishing in neuronal somata where APP is normally prominent.…”
Section: Study Conclusion Disease Implications and Therapeutic Opport...contrasting
confidence: 85%
“…For example, we have reported that deletion of presenilin, the protease responsible for the production of Aβ peptide from APP cleavage, markedly decreases the abundance of synaptotagmin‐7, a key calcium sensor involved in presynaptic plasticity 29 . We and others have also reported downregulation of presynaptic proteins in AD brains 30–32 including proteins determinant of cognitive reserve like complexin‐1 33,34 . This collection of data has led us to advocate for the hypothesis of presynaptic failure in AD 35 .…”
Section: Narrativementioning
confidence: 93%